2015
DOI: 10.1007/s11042-015-2649-7
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of brain images using wavelet-energy and biogeography-based optimization

Abstract: It is very important to early detect abnormal brains, in order to save social and hospital resources. The wavelet-energy was a successful feature descriptor that achieved excellent performances in various applications; hence, we proposed a novel wavelet-energy based approach for automated classification of MR brain images as normal or abnormal. SVM was used as the classifier, and biogeography-based optimization (BBO) was introduced to optimize the weights of the SVM. The results based on a 5×5-fold cross valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 156 publications
(71 citation statements)
references
References 33 publications
0
71
0
Order By: Relevance
“…Yang (2016) [13] presented a new approach respond to wavelet energy because WN shows excellent performance in practical application. The weights of SVM are optimized using BBO before classification.…”
Section: Methodsmentioning
confidence: 99%
“…Yang (2016) [13] presented a new approach respond to wavelet energy because WN shows excellent performance in practical application. The weights of SVM are optimized using BBO before classification.…”
Section: Methodsmentioning
confidence: 99%
“…Their accuracies were both 89.5%, which is higher than state-of-the-art methods. Future work will concentrate on the following five areas: (1) Extending our research to fruit images obtained in severe conditions, such as dried, sliced, tinned, canned, and partially covered; (2) Including additional relevant features (such as local binary patterns, wavelet-energy [41], spider-web-plot [42], wavelet packet transform, etc.) to enhance the classification performance; (3) Using interactive data mining [43], knowledge discovery [44] to test the proposed method; (4) Using compressed sensing techniques [45,46] to represent the image in sparsity domain; (5) Using advanced classification methods, like evolutionary methods inspired by Lamarch and Baldwin [29]; (6) Trying other activation functions such as ReLU.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Wang et al [20] proposed a combination of GA and KSVM to solve this problem. Yang et al [21] selected wavelet-energy as the features, and introduced biogeography-based optimization (BBO) to train the SVM. Wang et al [22] suggested to use stationary wavelet transform (SWT) to replace DWT, and then they proposed a hybridization of PSO and ABC (HPA) algorithm to train the classifier.…”
Section: Y Zhang Et Al / Abnormal Brain Detection By We and Qpsomentioning
confidence: 99%